On prejudices, judgments, and other topics in philosophy - Twardowski, Kazimierz, 1866-1938. (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2014)
The volume contains almost thirty papers by Kazimierz Twardowski (1866-1938), the founder of the Lvov-Warsaw School. The papers are published in English for the first time. They stem from the Lvov period, which is often contrasted with the earlier Vienna period of Twardowski's scientific activity. Contrary to received opinion, the editors argue that the Lvov period is just as important as the Vienna period. Indeed, the scope of Twardowski's investigations was much broader and more profound in later years. The papers concern fundamental problems of philosophy: the methods of philosophizing, the boundary of psychology and semiotics, the conceptual apparatus of metaphysics, ethical skepticism, the question of free will and ethical obligation, the aesthetics of music and so on. The systematic considerations are complemented by concise but excellent sketches of the philosophical views of Socrates, Aquinas, Leibniz, Spencer, Nietzsche, and Bergson.